Acting to Manage Conflict and Bullying Through Evidence-Based Strategies - Burton, B (Springer, 2015)
This book offers a complete and detailed account of the evolution of an internationally successful, evidence-based program that has been the result of almost two decades of action research into conflict and bullying. It addresses one of the most serious problems encountered in schools and work places worldwide: that of bullying and inter-personal conflict. The book presents a comprehensive account of the research, development and refinement of the DRACON Project and the Acting Against Bullying and Cooling Conflicts programs. The effective strategies that emerged from the extensive international research and practice use a combination of theories of conflict and bullying management with drama techniques and peer teaching which have been unique in their application. The book analyses their evolution into an effective program that has impacted positively on bullying and conflict in a number of settings. In the UK the program successfully addressed behavioural problems amongst girls in schools through the use of peer teaching in a drama setting. In Sweden the program assists nursing students, nurses and other health professionals to deal with conflict in the workplace. In Australia it has been applied in hundreds of schools to reduce bullying and assist newly arrived refugees to deal with cultural conflict and develop resilience and self- identity in their new country. This volume makes a major and authentic contribution to the international effort to find effective strategies and techniques to deal with interpersonal conflict and bullying across a range of contexts.